Preparation and application method of novel insulating material cross-linking agent

By using EAA and epoxy resin during the crosslinking process and introducing electron-absorbing groups, the problem of by-product generation in the traditional crosslinking method is solved, and the electron capture site of polymers is directly formed, which improves the thermal stability and voltage stability of the insulating material, and is suitable for high-voltage DC cable insulating materials.

CN119528850APending Publication Date: 2025-02-28HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311076718.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Traditional crosslinking methods produce harmful by-products during crosslinking, resulting in reduced electrical performance of cable insulation and poor thermal stability of existing insulating materials, limiting their application fields.

Method used

EAA is used as the matrix resin and epoxy resin is used as the crosslinking agent, and electron withdrawing groups are introduced during the crosslinking process, providing electron withdrawal induction and conjugation through the aromatic ring conjugation system, ensuring that there is no small molecule by-product generation in the crosslinking process and improving the voltage stability of the material.

Benefits of technology

It realizes no by-product generation during cross-linking, improves the molecular stability and voltage stability of the insulating material, enhances the thermal stability and mechanical properties of the material, and is suitable for high-voltage DC cable insulation materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528850A_ABST
    Figure CN119528850A_ABST
Patent Text Reader

Abstract

The invention relates to preparation and application methods of a novel insulating material cross-linking agent, and belongs to the technical field of insulating material preparation. The novel insulating material cross-linking agent is a bifunctional epoxy compound, and the specific preparation method is as follows: substituted hydroquinone and epichlorohydrin react in the presence of a phase transfer catalyst, then sodium hydroxide is added for cyclization, after-treatment is performed for suction filtration, ethyl acetate and water are used for washing, and finally rotary evaporation is performed to obtain a solid product. The epoxy compound obtained by the method can be used as a cross-linking agent of an EAA / LLDPE composite insulating material. The cross-linking agent has the advantages that the cross-linking process is simple, no small molecule by-product is generated in the cross-linking process, and the obtained insulating composite material is good in mechanical property, low in direct current conductivity, high in breakdown field strength and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation and application method of a novel insulating material crosslinking agent, belonging to the technical field of insulating material preparation. Background Art

[0002] The small molecule crosslinking agent added in the crosslinking process of the traditional crosslinking method will produce a certain amount of harmful byproducts. The harmful byproducts and dielectric impurities cause space charge accumulation. For example, the small molecule crosslinking agent diisopropylbenzene peroxide will decompose and produce four byproducts during the crosslinking process: methane, cumyl alcohol, acetophenone, and methyl styrene. Post-processing is usually required to remove the byproducts, and the process is complex and costly. These byproduct impurities can also cause the local electric field distortion in the cable insulation to multiply, which is one of the main factors that lead to the reduction of the electrical performance of the high-voltage DC cable insulation and is also an important evaluation indicator of the quality of the insulation material.

[0003] The present invention uses EAA as a base resin and epoxy resin as a crosslinking agent. No small molecule by-products are generated during the crosslinking process. Moreover, since the epoxy group in the crosslinking agent has a large reaction activity and the molar amount is much less than or equal to the active group carboxyl in EAA, it is ensured that all small molecule epoxy groups participate in the reaction and no by-products are generated.

[0004] In addition, the present invention introduces appropriate electron-withdrawing groups into the structure of the epoxy compound, especially introduces electron-withdrawing groups on the aromatic ring, provides strong electron-withdrawing induction and electron-withdrawing conjugation through the electron transfer of the aromatic ring conjugated system, gives full play to the ability of the electron-withdrawing group to "capture" electrons, and plays the role of a voltage stabilizer. In other words, the main purpose of the present invention is to first introduce appropriate electron-withdrawing groups on the small molecule cross-linking agent, and through the cross-linking reaction, the cross-linked high molecular polymer directly has electron capture sites, and the voltage stabilization effect can be achieved without the need to add an additional voltage stabilizer.

[0005] LLDPE has high impact strength, good electrical insulation and chemical resistance, but its field applicability is limited due to its poor thermal stability. LLDPE has poor processing performance and cannot be directly used as cable insulation material. It must be modified to meet the processing and application requirements of cables. The addition of EAA in the present invention can effectively make up for the defects of LLDPE, increase the molecular stability of the insulating material, and reduce the accumulation of space charges in the insulation. After LLDPE is modified, the thermal stability and mechanical properties of the material are greatly improved. Summary of the invention

[0006] The present invention utilizes substituted hydroquinone and epichlorohydrin to remove hydrogen chloride under the action of sodium hydroxide to generate a new type of aromatic glycidyl ether with an electron-withdrawing group, takes EAA-glycidyl ether cross-linked product and low-density polyethylene (LLDPE) as main substrates, utilizes the reaction characteristics of glycidyl ether and -COOH in EAA molecules to easily generate esters, and prepares a new epoxy composite material.

[0007] The technical solution of the present invention:

[0008] One of the purposes of the present invention is to provide a novel bifunctional epoxy compound, the structural formula of which is shown below:

[0009]

[0010] The preparation method is to react hydroquinone with epichlorohydrin in the presence of a certain amount of phase transfer catalyst for a period of time, then add a certain proportion of sodium hydroxide for cyclization reaction, perform post-treatment by suction filtration, then wash with ethyl acetate and water, and finally rotary evaporate to obtain a solid product. The specific reaction equation is as follows:

[0011]

[0012] It is further defined that R is: -CN, -Br, -Cl, -F.

[0013] The second object of the present invention is to provide a method for preparing the above composite material, which comprises the following steps:

[0014] S1, solution mixing: all raw materials are mixed into a solution.

[0015] S2, melt blending; blending the mixture evenly to obtain a mixed insulating material;

[0016] S3, processing and molding; pressing and molding the mixed insulating material in a flat vulcanizer, and then pressurizing and cross-linking, cooling and placing in a vacuum drying process to obtain an insulating composite material.

[0017] It is further defined that S1 specifically comprises: mixing several raw materials in solutions according to mass fractions of EAA 45-60%, LLDPE 30-50% and epoxy compound 5-10%.

[0018] It is further defined that S2 is specifically: adding the mixture into a torque rheometer at 110° C. and a rotation speed of 60 rpm and uniformly mixing for 10 minutes to obtain a composite material.

[0019] It is further defined that the pressing temperature in S3 is 120° C. and the pressure is 15 MPa.

[0020] It is further defined that the pressurized cross-linking temperature in S3 is 180° C. and the pressure is 15 MPa.

[0021] It is further defined that the vacuum drying treatment temperature in S3 is 80° C. and the time is 24 h.

[0022] A third object of the present invention is to provide an application of the composite material mentioned above, specifically the composite material is used to make a high voltage DC cable.

[0023] The present invention has the following beneficial effects:

[0024] (1) Two epoxy groups are introduced into the aromatic ring, which can be cross-linked with the polymer containing carboxyl groups. The formed ester polymerization points can effectively capture charges, and deep traps are introduced in situ by cross-linking.

[0025] (2) Aromatic compounds can effectively "capture" electrons, especially the introduction of "cyano" on the aromatic ring, which provides strong electron-withdrawing induction and electron-withdrawing conjugation effects, and can more effectively exert its ability to "capture" electrons and act as a voltage stabilizer.

[0026] (3) Use small molecule epoxy resin with strong reaction activity, while ensuring that the epoxy resin is not excessive, so that the cross-linking process does not produce cross-linking by-products, and meet the requirements of ultra-clean materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 NMR of 2,3-dicyanohydroquinone diglycidyl ether 1 HN MR;

[0028] Figure 2 This is the infrared spectrum of 2,3-dicyanohydroquinone diglycidyl ether;

[0029] Figure 3 Tensile test result curves of composite materials provided for different embodiments;

[0030] Figure 4 A comparative graph of infrared spectrum test results of composite materials provided in different embodiments;

[0031] Figure 5 Conductivity and current characteristic curves of composite materials provided for different embodiments; wherein (a) is ELQ, and (b) is ELM;

[0032] Figure 6 Weibull distribution diagram of breakdown field strength of composite materials provided for different embodiments; wherein (a) is ELQ, (b) is ELM; DETAILED DESCRIPTION

[0033] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0034] Embodiment 1:

[0035] The process of preparing the epoxy compound in this embodiment is as follows:

[0036] 2,3-dicyanohydroquinone, epichlorohydrin (1:18) and tetrabutylammonium bromide catalyst (5.0wt%) were measured in a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, the temperature was raised to 80°C and refluxed, the reaction was carried out for 5 hours, 40% sodium hydroxide (1:2.5) was added, and stirring was continued for a certain period of time after the addition until a large amount of solid was generated, petroleum ether was added and stirring was continued to precipitate the solid as much as possible, and then filtered and washed with ethyl acetate and water until the liquid became neutral, and finally the solid was evaporated under reduced pressure to remove epichlorohydrin to obtain the product with a yield of 79% and an epoxy value of 0.68 (theoretical epoxy value is 0.7).

[0037] Structure data: 1 H NMR (300 MHz, CDCl3, unit: ppm) δ7.30 (s, 2H), 4.47 (d, J = 9.8 Hz, 2H), 4.19–3.87 (m, 2H), 3.39 (s, 2H), 2.92 (dd, J = 22.6, 18.1 Hz, 4H).

[0038] IR(KBr):3095,2925,2231,1490,1286,1058,908cm -1 .

[0039] Embodiment 2:

[0040] The process of preparing the epoxy compound in this embodiment is as follows:

[0041] 2,3-Dibromohydroquinone, epichlorohydrin (1:18) and tetrabutylammonium bromide catalyst (5.0wt%) were measured in a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, the temperature was raised to 80°C and refluxed, the reaction was performed for 6 hours, 40% sodium hydroxide (1:2.5) was added, and stirring was continued for a certain period of time after the addition until a large amount of solid was generated, petroleum ether was added and stirring was continued to precipitate the solid as much as possible, and then filtered and washed with ethyl acetate and water until the liquid became neutral, and finally the epichlorohydrin was evaporated from the solid under reduced pressure to obtain the product with a yield of 73% and an epoxy value of 0.48 (theoretical epoxy value is 0.5).

[0042] Embodiment 3:

[0043] The process of preparing the epoxy compound in this embodiment is as follows:

[0044] 2,3-Dichlorohydroquinone, epichlorohydrin (1:18) and tetrabutylammonium bromide catalyst (5.0wt%) were measured in a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, the temperature was raised to 80°C and refluxed, the reaction was carried out for 8 hours, 40% sodium hydroxide (1:2.5) was added, and stirring was continued for a certain period of time after the addition until a large amount of solid was generated, petroleum ether was added and stirring was continued to precipitate the solid as much as possible, and then filtered and washed with ethyl acetate and water until the liquid became neutral, and finally the solid was evaporated under reduced pressure to remove epichlorohydrin to obtain the product with a yield of 75% and an epoxy value of 0.68 (theoretical epoxy value is 0.7).

[0045] Embodiment 4:

[0046] The process of preparing the epoxy compound in this embodiment is as follows:

[0047] 2,3-Difluorohydroquinone, epichlorohydrin (1:18) and tetrabutylammonium bromide catalyst (5.0wt%) were measured in a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, the temperature was raised to 80°C and refluxed, the reaction was performed for 8 hours, 40% sodium hydroxide (1:2.5) was added, and stirring was continued for a certain period of time after the addition until a large amount of solid was generated, petroleum ether was added and stirring was continued to precipitate the solid as much as possible, and then the mixture was filtered and washed with ethyl acetate and water until the liquid became neutral, and finally the epichlorohydrin was evaporated from the solid under reduced pressure to obtain the product with a yield of 78% and an epoxy value of 0.75 (theoretical epoxy value is 0.8).

[0048] Embodiment 5:

[0049] The process of preparing the composite material in this embodiment is as follows:

[0050] (1) Solution mixing: 22.5 g of EAA, 24.1 g of LLDPE and 3.4 g of 2,3-dicyanohydroquinone diglycidyl ether were placed in a dichloromethane solution and stirred evenly. The dichloromethane was then spin-dried and the mixture was air-dried.

[0051] (2) Melt blending: 50 g of the mixture was added into a torque rheometer, melted at 110° C., with a rotation speed of 60 r / min, and mixed for 10 min to obtain a blended insulating material.

[0052] (3) Processing and molding: The blended insulating material is pressed in a flat vulcanizer at a temperature of 120°C and a pressure of 15 MPa, and then pressed at a temperature of 180°C and a pressure of 15 MPa for 30 minutes to complete the cross-linking reaction, thereby obtaining a composite material - 45ELQ.

[0053] Embodiment 6:

[0054] The process of preparing the composite material in this embodiment is as follows:

[0055] (1) Solution mixing: 25 g of EAA, 21.2 g of LLDPE and 3.8 g of 2,3-dicyanohydroquinone diglycidyl ether were placed in a dichloromethane solution and stirred evenly. The dichloromethane was then spin-dried and the mixture was air-dried.

[0056] (2) Melt blending: 50 g of the mixture was added into a torque rheometer, melted at 110° C., with a rotation speed of 60 r / min, and mixed for 10 min to obtain a blended insulating material.

[0057] (3) Processing and molding: The blended insulating material is pressed in a flat vulcanizer at a temperature of 120°C and a pressure of 15 MPa, and then pressed at a temperature of 180°C and a pressure of 15 MPa for 30 min to complete the cross-linking reaction, thereby obtaining a composite material - 50ELQ.

[0058] Embodiment 7:

[0059] The process of preparing the composite material in this embodiment is as follows:

[0060] (1) Solution mixing: 27.5 g of EAA, 18.4 g of LLDPE and 4.1 g of 2,3-dicyanohydroquinone diglycidyl ether were placed in a dichloromethane solution and stirred evenly. The dichloromethane was then spin-dried and the mixture was air-dried.

[0061] (2) Melt blending: 50 g of the mixture was added into a torque rheometer, melted at 110° C., with a rotation speed of 60 r / min, and mixed for 10 min to obtain a blended insulating material.

[0062] (3) Processing and molding: The blended insulating material is pressed in a flat vulcanizer at a temperature of 120°C and a pressure of 15 MPa, and then pressed at a temperature of 180°C and a pressure of 15 MPa for 30 min to complete the cross-linking reaction, thereby obtaining a composite material - 55ELQ.

[0063] Embodiment 8:

[0064] The process of preparing the composite material in this embodiment is as follows:

[0065] (1) Solution mixing: 30 g of EAA, 15.5 g of LLDPE and 4.5 g of 2,3-dicyanohydroquinone diglycidyl ether were placed in a dichloromethane solution and stirred evenly. The dichloromethane was then spin-dried and the mixture was air-dried.

[0066] (2) Melt blending: 50 g of the mixture was added into a torque rheometer, melted at 110° C., with a rotation speed of 60 r / min, and mixed for 10 min to obtain a blended insulating material.

[0067] (3) Processing and molding: The blended insulating material is pressed in a flat vulcanizer at a temperature of 120°C and a pressure of 15 MPa, and then pressed at a temperature of 180°C and a pressure of 15 MPa for 30 min to complete the cross-linking reaction, thereby obtaining a composite material - 60ELQ.

[0068] Embodiment 9:

[0069] The process of preparing the composite material in this embodiment is as follows:

[0070] (1) Solution mixing: 22.5 g of EAA, 24.7 g of LLDPE and 2.8 g of resorcinol diglycidyl ether were placed in a dichloromethane solution and stirred evenly. The dichloromethane was spin-dried and the mixture was air-dried.

[0071] (2) Melt blending: 50 g of the mixture was added into a torque rheometer, melted at 110° C., with a rotation speed of 60 r / min, and mixed for 10 min to obtain a blended insulating material.

[0072] (3) Processing and molding: The blended insulating material is pressed in a flat vulcanizer at a temperature of 120°C and a pressure of 15 MPa, and then pressed at a temperature of 180°C and a pressure of 15 MPa for 30 minutes to complete the cross-linking reaction, thereby obtaining a composite material - 45ELM.

[0073] Embodiment 10:

[0074] The process of preparing the composite material in this embodiment is as follows:

[0075] (1) Solution mixing: 25 g of EAA, 22 g of LLDPE and 3 g of resorcinol diglycidyl ether were placed in a dichloromethane solution and stirred evenly. The dichloromethane was then spin-dried and the mixture was air-dried.

[0076] (2) Melt blending: 50 g of the mixture was added into a torque rheometer, melted at 110° C., with a rotation speed of 60 r / min, and mixed for 10 min to obtain a blended insulating material.

[0077] (3) Processing and molding: The blended insulating material is pressed in a flat vulcanizer at a temperature of 120°C and a pressure of 15 MPa, and then pressed at a temperature of 180°C and a pressure of 15 MPa for 30 minutes to complete the cross-linking reaction, thereby obtaining a composite material - 50ELM.

[0078] Embodiment 11:

[0079] The process of preparing the composite material in this embodiment is as follows:

[0080] (1) Solution mixing: 27.5 g of EAA, 19.1 g of LLDPE and 3.4 g of resorcinol diglycidyl ether were placed in a dichloromethane solution and stirred evenly. The dichloromethane was then spin-dried and the mixture was air-dried.

[0081] (2) Melt blending: 50 g of the mixture was added into a torque rheometer, melted at 110° C., with a rotation speed of 60 r / min, and mixed for 10 min to obtain a blended insulating material.

[0082] (3) Processing and molding: The blended insulating material is pressed in a flat vulcanizer at a temperature of 120°C and a pressure of 15 MPa, and then pressed at a temperature of 180°C and a pressure of 15 MPa for 30 minutes to complete the cross-linking reaction, thereby obtaining a composite material - 55ELM.

[0083] Embodiment 12:

[0084] The process of preparing the composite material in this embodiment is as follows:

[0085] (1) Solution mixing: 30 g of EAA, 16.3 g of LLDPE and 3.7 g of resorcinol diglycidyl ether were placed in a dichloromethane solution and stirred evenly. The dichloromethane was spin-dried and the mixture was air-dried.

[0086] (2) Melt blending: 50 g of the mixture was added into a torque rheometer, melted at 110° C., with a rotation speed of 60 r / min, and mixed for 10 min to obtain a blended insulating material.

[0087] (3) Processing and molding: The blended insulating material is pressed in a flat vulcanizer at a temperature of 120°C and a pressure of 15 MPa, and then pressed at a temperature of 180°C and a pressure of 15 MPa for 30 minutes to complete the cross-linking reaction, thereby obtaining a composite material - 60ELM.

[0088] Effect example:

[0089] The performance tests were performed on 45ELQ, 50ELQ, 55ELQ and 60ELQ and 45ELM, 50ELM, 55ELM and 60ELM prepared in Examples 5 to 12, respectively. The specific test process and results are as follows:

[0090] (1) The eight materials mentioned above were subjected to tensile tests using a tensile strength tester. The instrument was set with a clamp spacing of 20 mm and a tensile rate of 250 mm / min. Each material was tested 5 times. The results are as follows: Figure 3 shown.

[0091] Depend on Figure 3It can be seen that the stress-strain of the ELQ composite is better than that of the ELM composite, and the tensile effect of the ELQ composite with 60% EAA content is the best.

[0092] (2) The molecular structures of the above eight materials were tested, analyzed and characterized by Fourier transform infrared spectrometer (FT / IR 6100) to verify whether they successfully participated in the cross-linking reaction. The sample thickness selected in the experiment was 100 μm thin slices, and the test spectrum wave number range was 500-4000 cm -1 , scanning accuracy is 2cm -1 , the scanning times are 30 times, and the results are as follows Figure 4 shown.

[0093] Depend on Figure 4 It can be seen that compared with the EAA / LLDPE blend, the two modified composites have -1 A new absorption peak appeared near 1710 cm -1 The peak red-shifted to 1735 cm -1 , and turned into a broad peak, corresponding to the characteristic peak of the ester group in the composite material, indicating that the cross-linking was successful.

[0094] (3) According to the electric field strength and temperature of the insulation layer of the high-voltage DC cable during operation, the eight materials were subjected to a conductance current test on 200 μm samples at a field strength of 5 kV to 40 kV within the cable operating temperature range of 30 °C to obtain their EJ curves, as shown in Figure 2. Figure 5 As shown, the polarization time was set to 1 h.

[0095] Depend on Figure 5 It can be seen that under the same experimental conditions, the conductivity of the ELM composite is better than that of the ELQ, and with the increase of EAA content, the conductivity becomes worse. The conductivity of the ELM composite with 45% content at 20kV / mm is 1.74×10 -8 Reduced to 9.33×10 -10 .

[0096] (4) The DC breakdown field strength test of the above eight materials was carried out at 30°C using cylindrical electrodes, with a voltage step-up rate of 1 kV / s and a sample thickness of 100 μm. The samples and electrodes were all in transformer oil, and 10 groups of samples were selected for repeated experiments under each experimental condition.

[0097] The two-parameter Weibull distribution is used to perform statistics on the DC breakdown strength experimental data, which is described as follows:

[0098] P(E)=1-exp(-(E / Eb)β)

[0099] Where: P(E) is the cumulative failure probability, E is the measured breakdown field strength, Eb is the characteristic breakdown field strength when the breakdown probability is 63.2%, and β is the shape parameter.

[0100] The Weibull distribution of DC breakdown strength of the above eight materials is as follows: Figure 6 shown.

[0101] Depend on Figure 6 It can be seen that the characteristic breakdown field strength of the ELM composite material is higher than that of the ELQ composite material, and the breakdown field strength of the ELM composite material increases first and then decreases with the increase of the EAA content. When the EAA content is 50%, the characteristic breakdown field strength is the best, reaching a maximum value of 472.8kV / mm. The LLDPE / EAA modified composite material at this content has good stability.

Claims

1. The present invention relates to a preparation and application method of a novel insulating material crosslinking agent, characterized in that The novel insulating material crosslinking agent is a bifunctional epoxy compound, and its structure is shown in the following formula: Wherein R is: -CN, -Br, -Cl, -F; The preparation of the epoxy compound is achieved by the following method: substituted hydroquinone and epichlorohydrin are reacted for a period of time in the presence of a certain amount of phase transfer catalyst, sodium hydroxide is added for cyclization reaction, post-treatment is performed by suction filtration, washing with ethyl acetate and water, and finally rotary evaporation is performed to obtain a solid product. The epoxy compound obtained by the above method can be used as a cross-linking agent for various EAA / LLDPE composite insulating materials.

2. The preparation and application method of a novel insulating material crosslinking agent according to claim 1, characterized in that The substituted hydroquinone can be any one of the following compounds: 2,3-dicyanohydroquinone, 2,3-dibromohydroquinone, 2,3-dichlorohydroquinone, and 2,3-difluorohydroquinone.

3. The preparation and application method of a novel insulating material crosslinking agent according to claim 1, characterized in that The phase transfer catalyst can be tetraethylammonium bromide, tetrapropylammonium bromide, tetrabutylammonium bromide, tributylbenzylammonium bromide, etc.

4. The preparation and application method of a novel insulating material crosslinking agent according to claim 1, characterized in that The amount of the phase transfer catalyst used is 1-5% of the amount of the substituted phenol used.

5. The preparation and application method of a novel insulating material crosslinking agent according to claim 1, characterized in that The reaction time of the substituted hydroquinone and epichlorohydrin in the presence of a phase transfer catalyst is 5-8 hours.

6. The preparation and application method of a novel insulating material crosslinking agent according to claim 1, characterized in that The EAA / LLDPE composite insulating material comprises 45-60% EAA (DuPont 3002) and 30-50% LLDPE.

7. The preparation and application method of a novel insulating material crosslinking agent according to claim 1, characterized in that The epoxy compound is used as a cross-linking agent and the mass fraction added to the EAA / LLDPE composite insulating material is 5-10%.

8. The preparation and application method of a novel insulating material crosslinking agent according to claim 1, characterized in that The application of the new insulating material crosslinking agent is carried out according to the following method: after various materials are mixed according to a specific composition, they are added to a torque rheometer at 120°C and a rotation speed of 60rpm and mixed evenly for 10 minutes, pressed in a flat vulcanizer at a pressure of 15MPa, and then crosslinked at a certain temperature and a pressure of 15MPa for a certain time to obtain a composite material specimen for performance testing.

9. The preparation and application method of a novel insulating material crosslinking agent according to claims 1 and 8, characterized in that The cross-linking temperature is 160-180°C.

10. The preparation and application method of a novel insulating material crosslinking agent according to claims 1 and 8, characterized in that The cross-linking time is 30-45 minutes.